Method for preparing carbonized polymer nanodots

The preparation of carbonized polymer nanodots by spray drying method solves the problems of long reaction time, long purification time and low yield in the existing methods, and achieves high-efficiency and low-cost large-scale production.

CN119750554APending Publication Date: 2025-04-04QUZHOU INNOVATION INSTITUTION FOR CHEMICAL ENGINEERING & MATERIALS +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510079622.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-18
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing carbonized polymer nanodot preparation methods have long reaction time, long purification time, cumbersome operation, low yield and high equipment investment, making it difficult to achieve large-scale production.

Method used

Carbonized polymer nanodots were prepared by spray drying. By homogeneously mixing ascorbic acid and polyethyleneimine under ultrasound, adding nanozirconia, ball milling and spray drying, followed by dissolution, separation and freeze-drying.

Benefits of technology

This method can significantly save preparation time, improve efficiency, and increase the yield of carbonized polymer nanodots, while reducing the preparation cost and realizing the possibility of large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750554A_ABST
    Figure CN119750554A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of material preparation, and particularly relates to a method for preparing carbonized polymer nanodots, which comprises the following steps: adding ascorbic acid and polyethyleneimine into deionized water in proportion, then putting into an ultrasonic machine, completely dissolving the ascorbic acid and the polyethyleneimine, and uniformly mixing to obtain a mixed solution; adding nano zirconium oxide into the mixed solution obtained in the step S1, and performing ultrasonic treatment to prepare a uniform dispersion solution; placing the dispersion liquid in a ball mill for grinding to obtain slurry, carrying out reaction on the slurry through a spray dryer, and drying to prepare the zirconium oxide doped carbonized polymer nanodots; and S3, dissolving, separating and freeze-drying the dopant obtained in the step S3 to obtain the carbonized polymer nanodot. Compared with a hydrothermal method, the carbonized polymer nanodots prepared by the spray drying method can greatly save time, improve efficiency and increase the yield of the carbonized polymer nanodots.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material preparation, and in particular relates to a method for preparing carbonized polymer nanodots. Background Art

[0002] Carbonized polymer nanodots (CPDs) are usually formed from small molecules, polymers, or even biomass (such as leaves, fruit peels, and traditional Chinese medicine) containing various functional groups (amino, carboxyl, hydroxyl, ether bonds, etc.) as precursors, and undergo a series of processes such as polymerization, crosslinking, and carbonization through hydrothermal / solvothermal, microwave, and other methods to form CPDs. The carbon sources available for this type of method are very diverse, which also leads to the fact that the prepared CPDs usually have various different properties, but they generally have an amorphous carbon core and a variety of rich functional groups on the surface, making them stable and easy to modify, and convenient for functionalization. Precursors containing elements such as N, S, and P are often selected during the preparation process to enhance the performance of CPDs. The CPDs prepared by this method have a high quantum yield, do not require expensive equipment and complex preparation processes, and are easy to achieve large-scale production.

[0003] At present, there are many methods for preparing carbonized polymer nanodots, and the common methods are: hydrothermal / solvothermal, microwave method, etc. Yang Bai's research group at Jilin University first reported a method for preparing carbonized polymer nanodots by hydrothermal method. They used small molecule citric acid as a carbon source and added ethylenediamine as a nitrogen source. They prepared CPDs with a fluorescence quantum yield of up to 80% by hydrothermal method, which exceeded all previously reported carbon-based fluorescent materials and was comparable to fluorescent dyes. In addition, the yield was about 60%.

[0004] J IANG L, CAI H, ZHOU W, et al. RNA-targeting carbon dots for live-cell imaging of granuledynami cs[J]. Advanced Materials, 2023, 35(21): 2210776. Red luminescent CPDs were synthesized by using neutral red and levofloxacin as precursors and 800W microwave heating for 7 min. The CPDs have good water solubility, an average particle size of only 1.6nm, a fluorescence quantum yield of 22.83%, and the emission wavelength is independent of the excitation wavelength.

[0005] In the above preparation methods, there are disadvantages such as long reaction time, long purification time, cumbersome operation, high product loss, and low yield, and the microwave method has high equipment investment, which is difficult to achieve the needs of large-scale production. Therefore, in view of the shortcomings of the existing methods, a preparation method of carbonized polymer nanodots with simple process flow, short time, low cost and easy mass production is needed. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing carbonized polymer nanodots in order to solve the above-mentioned technical problems, thereby saving time, improving efficiency and increasing the yield of carbonized polymer nanodots.

[0007] In view of this, the present invention provides a method for preparing carbonized polymer nanodots, comprising the following steps:

[0008] S1: adding ascorbic acid and polyethyleneimine into deionized water in proportion, and then putting the mixture into an ultrasonic machine to completely dissolve the ascorbic acid and polyethyleneimine and uniformly mix them to obtain a mixed solution;

[0009] S2: adding nano zirconium oxide to the mixed solution obtained in step S1, and ultrasonically preparing the mixed solution into a uniform dispersion;

[0010] S3: grinding the dispersion in a ball mill to obtain a slurry, and reacting and drying the slurry in a spray dryer to prepare zirconium oxide-doped carbonized polymer nanodots;

[0011] S4: dissolving, separating and freeze-drying the dopant obtained in step S3 to obtain carbonized polymer nanodots.

[0012] In the present technical solution, the carbonized polymer nanodots prepared by the spray drying method can greatly save time and improve efficiency compared with the hydrothermal method, and can also increase the yield of the carbonized polymer nanodots.

[0013] Furthermore, in step S1, the mass ratio of ascorbic acid to polyethyleneimine is 1:5-5:1.

[0014] Furthermore, in step S1, the mass ratio of ascorbic acid to polyethyleneimine is 2:1.

[0015] In the technical solution, when the mass ratio of ascorbic acid to polyethyleneimine is 2:1, the fluorescence intensity of the obtained carbonized polymer nanodots can be significantly increased under 365nm ultraviolet light excitation.

[0016] Furthermore, the content of deionized water in step S1 is 150-300 mL.

[0017] Furthermore, in step S2, the mass of zirconium oxide is 20-80 g.

[0018] Furthermore, in step S3, a spray dryer is used for reaction and drying, the temperature is 200-280° C., the peristaltic pump feed rate is 750 mL / h-1200 mL / h, and the needle passage time is 5-10 s.

[0019] Furthermore, in step S4, the dopant is dissolved in deionized water, and the content of the deionized water used is 50-200 mL.

[0020] Furthermore, the separation in step S4 is performed using a centrifuge.

[0021] Furthermore, the centrifuge speed used for separation in step S4 is 8000-11000 rpm and the time is 15 min.

[0022] Furthermore, the freezing in step S4 uses a vacuum freeze dryer.

[0023] Furthermore, in step S4, the mixture is placed in a vacuum freeze dryer for freeze drying for 36-60 hours.

[0024] The beneficial effects of the present invention are:

[0025] 1. Compared with the hydrothermal method, the carbonized polymer nanodots prepared by the spray drying method can greatly save time, improve efficiency, and increase the yield of carbonized polymer nanodots.

[0026] 2. When the mass ratio of ascorbic acid to polyethyleneimine is 2:1, the fluorescence intensity of the obtained carbonized polymer nanodots can be significantly increased under 365nm ultraviolet light excitation. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a transmission electron microscopy image of the carbonized polymer nanodots prepared in Example 1;

[0028] Figure 2 This is a physical picture of the carbonized polymer nanodots prepared in Example 1;

[0029] Figure 3 This is the XRD pattern of the carbonized polymer nanodots prepared in Example 1;

[0030] Figure 4 This is the UV FT-IR spectrum of the carbonized polymer nanodots prepared in Example 1;

[0031] Figure 5 The ultraviolet absorption spectrum of the carbonized polymer nanodots prepared in Example 1;

[0032] Figure 6 The fluorescence emission spectrum of the carbonized polymer nanodots prepared in Example 1 under 365nm ultraviolet light excitation;

[0033] Figure 7 The fluorescence emission spectra of carbonized polymer nanodots prepared at different mass ratios of ascorbic acid and polyethyleneimine as raw materials in Examples 1, 2 and 3 under 365 nm ultraviolet light excitation;

[0034] Figure 8 The fluorescence emission spectra of the carbonized polymer nanodots prepared at different temperatures in Examples 1, 4 and 5 under 365 nm ultraviolet light excitation. DETAILED DESCRIPTION

[0035] The following will be combined with the drawings in the embodiments of the present application to clearly describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments in the present application belong to the scope of protection of this application.

[0036] In the description of the present application, it should be noted that the terms used herein are only for describing specific embodiments, and are not intended to limit the exemplary embodiments according to the present application. For ease of description, the sizes of the various parts shown in the drawings are not drawn according to the actual proportional relationship. The technology, methods and equipment known to ordinary technicians in the relevant field may not be discussed in detail, but in appropriate cases, the technology, methods and equipment should be regarded as part of the authorization specification. In all examples shown and discussed here, any specific value should be interpreted as merely exemplary, rather than as a limitation. Therefore, other examples of the exemplary embodiments may have different values. It should be noted that similar numbers and letters represent similar items in the following drawings, so once an item is defined in one drawing, it does not need to be further discussed in subsequent drawings.

[0037] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not used to describe a specific order or sequence. It should be understood that the data used in this way can be interchangeable under appropriate circumstances, so that the embodiments of the present application can be implemented in an order other than those illustrated or described here, and the objects distinguished by "first", "second", etc. are generally of one type, and the number of objects is not limited. For example, the first object can be one or more. In addition, "and / or" in the specification and claims represents at least one of the connected objects, and the character " / " generally indicates that the objects associated with each other are in an "or" relationship.

[0038] It should be noted that, in the description of the present application, the orientation or positional relationship indicated by terms such as "front, back, up, down, left, right", "lateral, vertical, perpendicular, horizontal" and "top, bottom" are usually based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present application and simplifying the description. Unless otherwise stated, these orientation words do not indicate or imply that the device or element referred to must have a specific orientation or be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the scope of protection of the present application; the orientation words "inside and outside" refer to the inside and outside relative to the contour of each component itself.

[0039] It should be noted that, in the present application, the terms "comprise", "include" or any other variant thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises one..." does not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be noted that the scope of the method and device in the embodiment of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.

[0040] A method for preparing carbonized polymer nanodots comprises the following steps:

[0041] S1. Add ascorbic acid and polyethyleneimine into deionized water in a certain proportion, and place the mixture in an ultrasonic machine to completely dissolve and evenly mix the two reactants;

[0042] S2, weighing a certain amount of nano zirconium oxide and adding it to the above mixed solution, and ultrasonically configuring it into a uniformly dispersed solution;

[0043] S3, grinding the dispersion in a ball mill to obtain a slurry, reacting and drying the slurry in a spray dryer to prepare a large number of zirconium oxide-doped carbonized polymer nanodots;

[0044] S4. Dissolving, separating and freeze-drying the obtained dopant to obtain carbonized polymer nanodots.

[0045] In certain embodiments, in step S1, the mass ratio of ascorbic acid to polyethyleneimine is 1:5-5:1, including but not limited to 1:4, 1:3, 1:2, 2:5, 2:4, 2:3, 2:1, 3:5, 3:4, 3:2, 3:1, 4:5, 4:3, 4:1, 1:1, 5:4, 5:3, 5:2, 5:1.

[0046] In certain embodiments, in step S1, the volume of deionized water is 150-300 mL, including but not limited to 150-175 mL, 150-200 mL, 150-225 mL, 150-250 mL, 150-275 mL, 175-300 mL, 175-200 mL, 175-225 mL, 175-250 mL, 175-275 mL, 200-300 mL, 200-225 mL, 200-250 mL, 200-275 mL, 225-250 mL, 225-275 mL, 225-300 mL, 250-275 mL, 250-300 mL, 275-300 mL.

[0047] In certain embodiments, in step S2, the mass of the zirconium oxide is 20-80g, including but not limited to 20-70g, 20-60g, 20-50g, 20-40g, 20-30g, 30-80g, 30-70g, 30-60g, 30-50g, 30-40g, 40-80g, 40-70g, 40-60g, 40-50g, 50-80g, 50-70g, 50-60g, 60-80g, 60-70g, 70-80g.

[0048] In certain embodiments, in step S3, the reaction and drying are carried out using a spray dryer at a temperature of 200-280°C, including but not limited to 200-270°C, 200-260°C, 200-250°C, 200-240°C, 200-230°C, 200-220°C, 200-210°C, 210-220°C, 210-230°C, 210-240°C, 210-250°C, 210-260°C, 210-270°C, 210-280°C, 220-280°C, 220-270°C, 220-260°C, 2 20-250℃, 220-240℃, 220-230℃, 230-280℃, 230-270℃, 230-260℃, 230-250℃, 230-240℃, 240-280℃, 240-270℃, 240-260℃, 240-250℃, 250-280℃, 250-270℃, 250-260℃, 260-280℃, 260-270℃, 270-280℃, the peristaltic pump feed is 25-40% (the maximum feed rate 100% is 3000mL / h), and the needle passage time is 5-10s.

[0049] In some embodiments, the content of deionized water used to dissolve the dopant in step S4 is 50-200 mL.

[0050] In certain embodiments, the centrifuge speed used for separation in step S4 is 8000-11000 rpm, including but not limited to 8000-10000 rpm, 8000-9000 rpm, 9000-11000 rpm, 9000-10000 rpm, 10000-11000 rpm, and the time is 15 min.

[0051] In certain embodiments, freeze drying in a vacuum freeze dryer in step S4 is performed for 36-60 hours.

[0052] Embodiment 1

[0053] Ascorbic acid and polyethyleneimine are added to 150 mL of deionized water in a mass ratio of 2:1 (the sum of the mass of ascorbic acid and polyethyleneimine is 15 g), and the mixed solution is placed in an ultrasonic machine and stirred to completely dissolve and evenly mix; 20 g of zirconium oxide with a particle size of 40 nm is weighed and added to the above mixed solution, and ultrasonically configured into a uniformly dispersed solution; the dispersed solution is placed in a ball mill for grinding, and the resulting slurry is reacted and dried by a spray dryer, and the spray dryer parameter temperature is 200°C, the peristaltic pump feed is 25%, and the needle passing time is 5 seconds to obtain a mixture of zirconium oxide doped with carbonized polymer nanodots; the dopant is dissolved in 100 mL of deionized water, centrifuged at 10000 rpm for 10 minutes, and then separated, and the supernatant is placed in a culture dish for freeze drying for 36 hours to obtain carbonized polymer nanodots.

[0054] Embodiment 2

[0055] Ascorbic acid and polyethyleneimine are added to 150 mL of deionized water in a mass ratio of 3:1 (the sum of the mass of ascorbic acid and polyethyleneimine is 20 g), and the mixed solution is placed in an ultrasonic machine and stirred to completely dissolve and evenly mix; 20 g of zirconium oxide with a particle size of 40 nm is weighed and added to the above mixed solution, and ultrasonically configured into a uniformly dispersed solution; the dispersed solution is placed in a ball mill for grinding, and the resulting slurry is reacted and dried in a spray dryer, and the spray dryer parameter temperature is 200°C, the peristaltic pump feed is 25%, and the needle passing time is 5 seconds to obtain a mixture of zirconium oxide doped with carbonized polymer nanodots; the dopant is dissolved in 100 mL of deionized water, centrifuged at 10000 rpm for 10 minutes, and then separated, and the supernatant is placed in a culture dish for freeze drying for 36 hours to obtain carbonized polymer nanodots.

[0056] Embodiment 3

[0057] Ascorbic acid and polyethyleneimine are added to 150 mL of deionized water in a mass ratio of 3:2 (the sum of the mass of ascorbic acid and polyethyleneimine is 25 g), and the mixed solution is placed in an ultrasonic machine and stirred to completely dissolve and evenly mix; 20 g of zirconium oxide with a particle size of 40 nm is weighed and added to the above mixed solution, and ultrasonically configured into a uniformly dispersed solution; the dispersed solution is placed in a ball mill for grinding, and the resulting slurry is reacted and dried in a spray dryer, and the spray dryer parameter temperature is 200°C, the peristaltic pump feed is 25%, and the needle passing time is 5 seconds to obtain a mixture of zirconium oxide doped with carbonized polymer nanodots; the dopant is dissolved in 100 mL of deionized water, centrifuged at 10000 rpm for 10 minutes, and then separated, and the supernatant is placed in a culture dish for freeze drying for 36 hours to obtain carbonized polymer nanodots.

[0058] Embodiment 4

[0059] Ascorbic acid and polyethyleneimine are added to 150 mL of deionized water in a mass ratio of 2:1 (the sum of the mass of ascorbic acid and polyethyleneimine is 15 g), and the mixed solution is placed in an ultrasonic machine and stirred to completely dissolve and evenly mix; 20 g of zirconium oxide with a particle size of 40 nm is weighed and added to the above mixed solution, and ultrasonically configured into a uniformly dispersed solution; the dispersed solution is placed in a ball mill for grinding, and the resulting slurry is reacted and dried in a spray dryer, and the spray dryer parameter temperature is 150°C, the peristaltic pump feed is 25%, and the needle passing time is 5 seconds to obtain a mixture of zirconium oxide doped with carbonized polymer nanodots; the dopant is dissolved in 100 mL of deionized water, centrifuged at 10000 rpm for 10 minutes, and then separated, and the supernatant is placed in a culture dish for freeze drying for 36 hours to obtain carbonized polymer nanodots.

[0060] Embodiment 5

[0061] Ascorbic acid and polyethyleneimine are added to 150 mL of deionized water in a mass ratio of 2:1 (the sum of the mass of ascorbic acid and polyethyleneimine is 15 g), and the mixed solution is placed in an ultrasonic machine and stirred to completely dissolve and evenly mix; 20 g of zirconium oxide with a particle size of 40 nm is weighed and added to the above mixed solution, and ultrasonically configured into a uniformly dispersed solution; the dispersed solution is placed in a ball mill for grinding, and the resulting slurry is reacted and dried in a spray dryer, and the spray dryer parameter temperature is 250°C, the peristaltic pump feed is 25%, and the needle passing time is 5 seconds to obtain a mixture of zirconium oxide doped with carbonized polymer nanodots; the dopant is dissolved in 100 mL of deionized water, centrifuged at 10000 rpm for 10 minutes, and then separated, and the supernatant is placed in a culture dish for freeze drying for 36 hours to obtain carbonized polymer nanodots.

[0062] Comparative Example 1

[0063] Ascorbic acid and polyethyleneimine were added into 150 mL of deionized water in a mass ratio of 2:1 (the sum of the mass of ascorbic acid and polyethyleneimine was 15 g), and the mixture was placed in an ultrasonic machine and stirred to completely dissolve and evenly mix; 20 g of zirconium oxide with a particle size of 40 nm was weighed and added into the above mixture, and ultrasonically configured into a uniformly dispersed solution; the dispersion was placed in a ball mill for grinding, and the obtained slurry was added into a 500 mL hydrothermal reactor, and the hydrothermal reactor was placed at 200°C for reaction for 10 hours , a mixture of zirconium oxide doped with carbonized polymer nanodots is obtained; the dopant is dissolved in 100 mL of deionized water, centrifuged at 10000 rpm for 10 min, and then separated, the supernatant is taken, and filtered using a 0.22 μm microporous injection filter; the filtrate is poured into a dialysis bag, and dialyzed and purified in a large amount of ultrapure water for 48 hours, during which the ultrapure water is replaced in time; after the dialysis is completed, the N-CPDs dispersion is placed in a vacuum freeze drying box and freeze-dried for 60 hours to obtain a brown powder, which is sealed and stored in a refrigerator.

[0064]

[0065] It can be seen from Examples 1 to 5 and Comparative Example 1 that the carbonized polymer nanodots prepared by the spray drying method of the present application can greatly save time and improve efficiency compared to the hydrothermal method, and at the same time can increase the yield of carbonized polymer nanodots. It can be seen from Examples 1 and 2 that when the mass ratio of ascorbic acid to polyethyleneimine is 2:1, the fluorescence intensity of the obtained carbonized polymer nanodots under 365nm ultraviolet light excitation can be significantly increased. In the prior art, the preparation of carbonized polymer nanodots is mainly hydrothermal, and the purification method is mainly dialysis, which is time-consuming and cumbersome to operate, and the product loss is also large. There is no certain standard for the use of dialysis bags, which makes it difficult for carbonized polymer nanodots to achieve industrial production. The present invention uses spray drying to achieve rapid production of carbonized polymer nanodots, and determines the effects of various control conditions on product performance, thereby preparing high-quality carbonized polymer nanodots suitable for application.

[0066] The embodiments of the present application are described above in conjunction with the accompanying drawings. In the absence of conflict, the embodiments in the present application and the features in the embodiments can be combined with each other. The present application is not limited to the above-mentioned specific implementation methods. The above-mentioned specific implementation methods are merely illustrative and not restrictive. Under the guidance of the present application, ordinary technicians in this field can also make many forms without departing from the purpose of the present application and the scope of protection of the claims, all of which are within the protection of the present application.

Claims

1. A method for preparing carbonized polymer nanodots, characterized in that , including the following steps: S1: adding ascorbic acid and polyethyleneimine into deionized water in proportion, and then putting the mixture into an ultrasonic machine to completely dissolve the ascorbic acid and polyethyleneimine and uniformly mix them to obtain a mixed solution; S2: adding nano zirconium oxide to the mixed solution obtained in step S1, and ultrasonically preparing the mixed solution into a uniform dispersion; S3: grinding the dispersion in a ball mill to obtain a slurry, and reacting and drying the slurry in a spray dryer to prepare zirconium oxide-doped carbonized polymer nanodots; S4: dissolving, separating and freeze-drying the dopant obtained in step S3 to obtain carbonized polymer nanodots.

2. The method for preparing carbonized polymer nanodots according to claim 1, characterized in that: In step S1, the mass ratio of ascorbic acid to polyethyleneimine is 1:5-5:

1.

3. The method for preparing carbonized polymer nanodots according to claim 1, characterized in that: The mass ratio of ascorbic acid to polyethyleneimine in step S1 is 2:

1.

4. The method for preparing carbonized polymer nanodots according to claim 1, characterized in that: The content of deionized water in step S1 is 150-300 mL.

5. The method for preparing carbonized polymer nanodots according to claim 1, characterized in that: The mass of zirconium oxide in step S2 is 20-80g.

6. The method for preparing carbonized polymer nanodots according to claim 1, characterized in that: In step S3, a spray dryer is used for reaction and drying, the temperature is 200-280° C., the peristaltic pump feed rate is 750 mL / h-1200 mL / h, and the needle passage time is 5-10 s.

7. The method for preparing carbonized polymer nanodots according to claim 1, characterized in that: In step S4, the dopant is dissolved in deionized water, and the content of the deionized water used is 50-200 mL.

8. The method for preparing carbonized polymer nanodots according to claim 1, characterized in that: The separation in step S4 is performed using a centrifuge.

9. The method for preparing carbonized polymer nanodots according to claim 1, characterized in that: The centrifuge speed used for separation in step S4 is 8000-11000 rpm and the time is 15 min.

10. The method for preparing carbonized polymer nanodots according to claim 1, characterized in that: The vacuum freeze dryer used in step S4 has a freeze drying time of 36-60 hours.

Citation Information

Patent Citations

  • Rapid preparation method of carbon quantum dots

    CN107934936A

  • Polyethyleneimine modified ascorbic acid carbon nanodots, preparation method and application

    CN109991200A

  • Efficient preparation method of nitrogen-doped functionalized carbon quantum dots

    CN111454714A

  • Method for preparing nano zirconium dioxide carbon quantum dot composite material by one-pot method

    CN112210365A

  • Method for preparing carbonized polymer quantum dots through spray pyrolysis

    CN113247879A